Demographic features, laboratory findings and outcomes of ICU patients with COVID-19 in Ahvaz, Iran: A single-centered prospective study - Maryam Haddad Zadeh Shoushtari; Neda Safapour; Mohsen Savaie; Hanieh Raji; Bahman Cheraghian (Journal of Family Medicine and Primary Care)
Background: COVID-19 can lead to severe acute respiratory syndrome so that some patients need to be admitted to the Intensive Care Unit (ICU). The aim of the current study is to investigate the frequency of demographic, laboratory and imaging findings and type of treatment and their relationship with disease outcomes in patients with COVID-19. Material and Methods: This prospective cross-sectional study was conducted on all patients with COVID-19 who were admitted in the ICU of Razi Hospital in Ahvaz, Iran from January 20 to February 20, 2021. Patient information including demographic features, laboratory and imaging findings and clinical outcomes was recorded. Results: One hundred and thirty-three patients were recruited in the present study, out of which 74 patients (55.6%) were males and 59 patients (44.4%) were females. The overall mortality rate of patients was 35.3% (47 patients) and was higher in patients over 65 years of age. There was a significant difference in terms of thrombocytopenia (P value: 0.001), lymphopenia (P value: 0.004), progression of lung involvement in imaging, shock, disseminated intravascular coagulation (DIC), sepsis and receiving invasive respiratory support in living and deceased patients (P value < 0.001). Furthermore, the difference in life status and the length of in-ICU stay in patients with hyperkalemia and renal failure was statistically significant (P value = 0.033, P value < 0.001 respectively). Conclusion: Mortality rate of patients with COVID- 19 admitted to ICU is generally high. According to the findings of this study, thrombocytopenia, lymphopenia, hyperkalemia and AKI are laboratory disorders associated with increased mortality. Moreover, the progression of pulmonary involvement in imaging, shock, DIC, sepsis, and need to invasive respiratory support is associated with low survival of patients.